Framework for analysis and improvement of data-fusion algorithms - Nassar, Mohammad Othman; Kanaan, Ghassan; Awad, Hussain A H (2010 2nd IEEE International Conference on Information Management and Engineering, 2010)
The data-fusion techniques have been investigated by many researchers and have been used in implementing several information retrieval systems. Introducing a new or improved data-fusion algorithm is an active research area for the researchers' community. We propose a framework for analyses and improvement of Data-fusion algorithms; this framework is going to be: First; a supportive tool for researchers when they are going to design a new Data-fusion algorithm by providing them with an extensive analysis and refinement for their new fusion algorithms, second; it can help researchers in understanding, analyzing, and improving existing Data-fusion algorithms.